Pemanfaatan PhET Simulation untuk Meningkatkan Pemahaman Fisika Peserta Didik Kelas XII MIPA pada Materi Listrik Arus Searah - Riana Sari (Institute of Advanced Knowledge and Science, 2023)
Physics is a subject that is considered difficult by many students. The large amount of calculations and the difficulty of visualizing the concepts being learned can make it challenging. As a result, many students feel that they do not understand Physics well. This problem can be addressed, in part, by using appropriate learning media. For the topic of direct current electricity, the author used a virtual Lab based on the PhET Simulation, to make it easier for students to understand the concepts being learned. This research was conducted on XII MIPA class students at SMAN 5 Tangerang Regency, and the results showed a significant improvement in student understanding, with an N-Gain score of 0.71, which is in the high category and effective in improving student understanding.